Difference between revisions of "The Phase Rule"

From Soft-Matter
Jump to: navigation, search
Line 3: Line 3:
  
  
 +
<math>\begin{align}
 +
  & p_{a}=p_{b}=\ldots =p_{P} \\
 +
& T_{a}=T_{b}=\ldots =T_{P} \\
 +
& \mu _{ia}=\mu _{ib}=\ldots =\mu _{iP};\text{    }i=1,2,\ldots C \\
 +
\end{align}</math>
  
 +
<math>=\left( P-1 \right)\left( C+2 \right)</math>
 +
 +
 +
<math>F=\left( C+1 \right)P-\left( P-1 \right)\left( C+2 \right)=C+2-P</math>
 +
 +
<math>F=C+2-P</math>
  
  

Revision as of 22:10, 7 November 2008

Back to Topics.


<math>\begin{align}

 & p_{a}=p_{b}=\ldots =p_{P} \\ 
& T_{a}=T_{b}=\ldots =T_{P} \\ 
& \mu _{ia}=\mu _{ib}=\ldots =\mu _{iP};\text{    }i=1,2,\ldots C \\ 

\end{align}</math>

<math>=\left( P-1 \right)\left( C+2 \right)</math>


<math>F=\left( C+1 \right)P-\left( P-1 \right)\left( C+2 \right)=C+2-P</math>

<math>F=C+2-P</math>



Back to Topics.